Critical Distance in Documentary Media (Springer International Publishing, 2018)
This collection of essays presents new formulations of ideas and practices within documentary media that respond critically to the multifaceted challenges of our age. As social media, augmented reality, and interactive technologies play an increasing role in the documentary landscape, new theorizations are needed to account for how such media both represents recent political, socio-historical, environmental, and representational shifts, and challenges the predominant approaches by promoting new critical sensibilities. The contributions to this volume approach the idea of "critical distance" in a documentary context and in subjects as diverse as documentary exhibitions, night photography, drone imagery, installation art, mobile media, nonhuman creative practices, sound art and interactive technologies. It is essential reading for scholars, practitioners and students working in fields such as documentary studies, film studies, cultural studies, contemporary art history and digital media studies.